Influence of Nutrients and Nutrient Use Efficient Genotypes on Tuber and Leaf Cyanogen and Tuber Starch in Cassava - T. R., Sruthi; N., Nooruniza; K., Susan John; J., Sreekumar; M. N., Sheela (JOURNAL OF ROOT CROPS, 2019)
The present study reports the variation in tuber quality parameters like starch, cyanogenic glucosides (CN) and leaf CN content among four nutrient use efficient (NUE) cassava genotypes viz., Sree Pavithra, CI-905, CI-906 and 7 III E3-5. The impact of secondary nutrient Mg and micronutrients viz., Zn and B on the above parameters in cassava variety Sree Visakham (H-1687) towards the later period of maturity of cassava also was studied. Among the genotypes, Sree Pavithra had the least and 7 III E3- 5 had the highest tuber CN. A decreasing trend in tuber CN from 7-9 months after planting (MAP) was recorded in the genotypes. The leaf CN was very high compared to tuber CN. The highest leaf CN was in 7 III E3-5 as in the case of tuber CN. The genotype CI-906 had the lowest leaf CN followed by Sree Pavithra. But the leaf CN increased at 9 MAP compared to 7 and 8 MAP. There was a positive correlation between tuber and leaf CN. In the case of tuber starch, there was a significant difference among genotypes with Sree Pavithra on par with CI-906, having the highest, and 7 III E3-5 on par with CI-905 having lower starch contents. However, there was a significant increase during 8-8.5 MAP. As regards to the influence of secondary and micronutrients, compared to PoP, different combinations of these nutrients resulted in significantly low tuber CN which in turn were on par. The stage of plant growth did not impact on tuber CN. Leaf CN was considerably lowered due to the application of secondary and micronutrients. Compared to PoP, the leaf CN was highest under three nutrient combination of Mg, Zn and B as well as Zn along with Mg. A sharp decline in leaf CN was also noticed from7 to 9 MAP. Significant positive correlation was seen between tuber and leaf CN. In the case of tuber starch, application of Mg along with Zn resulted in significantly the highest tuber starch whereas application of Mg alone, resulted the lowest. Significant negative correlation was seen between tuber starch and tuber CN and between tuber starch and leaf CN.